PENGARUH WAKTU PENYIMPANAN DAN METODE PENGERINGAN TERHADAP STABILITAS PARAMETER PROKSIMAT BATUBARA: Indonesia - Muhajir, Achmad; Iryani, A. Sry (UIR Press, 2026)
This study aims to analyze the effect of storage time and drying methods on the stability of coal proximate parameters. The parameters observed include moisture, ash, volatile matter, and fixed carbon. The experiment was conducted using storage time variations (0, 1, 2, 3, and 4 weeks) and drying methods (oven at 105°C and microwave at 300–600 W). Proximate analysis was performed based on ASTM standards. Data were analyzed using two-way ANOVA to determine the significance of the variables. The results showed that storage time significantly affected all proximate parameters, particularly increasing moisture content and decreasing volatile matter. The microwave method reduced moisture more effectively but caused greater changes in volatile matter and fixed carbon. In contrast, the oven method produced more stable and representative results. Therefore, the oven method is recommended for coal proximate analysis..